1989
DOI: 10.1002/anie.198910161
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Reactivity of Silicon–Sulfur and Silicon–Selenium Double Bonds. The First X‐Ray Structure of a Silanethione

Abstract: Silanethione 2a and silaneselenone 2b—stabilized by intramolecular Si ← N coordination— are obtained as shown below. The X‐ray structure analysis of 2a, 1‐naphthyl instead of phenyl, reveals strong zwitterionic character, which might explain the unexpectedly low reactivity toward nucleophiles and electrophiles (a, X = S; b, X = Se).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 44 publications
5
65
0
2
Order By: Relevance
“…[3,4] Even the intramolecular N-donor-supported silanechalcogenones I (dA C H T U N G T R E N N U N G ( 29 Si) = 22.3 ppm) and II (dA C H T U N G T R E N N U N G ( 29 Si) = 29.4 ppm) [2] are less shielded than 3 a,b and 4 a,b, respectively. Apparently, this observation is indicative of greater perturbation of the Si=E (E= O, S, Se, Te) double bonds caused by both the C 3 N 2 p system in the backbone and the NHC moiety, thereby leading to several resonance structures as depicted in Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] Even the intramolecular N-donor-supported silanechalcogenones I (dA C H T U N G T R E N N U N G ( 29 Si) = 22.3 ppm) and II (dA C H T U N G T R E N N U N G ( 29 Si) = 29.4 ppm) [2] are less shielded than 3 a,b and 4 a,b, respectively. Apparently, this observation is indicative of greater perturbation of the Si=E (E= O, S, Se, Te) double bonds caused by both the C 3 N 2 p system in the backbone and the NHC moiety, thereby leading to several resonance structures as depicted in Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Since Corriu et al reported in 1989 the first stable silanethione (Si=S) and silaneselone (Si=Se) derivatives I and II (Scheme 1) supported by a intramolecular N! Si donor-acceptor bond, [2] several series of stable doubly bonded species have been developed by taking advantage of the kinetic protection from the bulky ligands and/or the thermodynamic stabilization from Lewis donors as well as acceptors. Striking examples, including a series of fascinating stable heavier diarylsilanechalcogenones III (Scheme 1) [3] and dialkylsilanechalcogenones IV (Scheme 1) [4] without intramolecular donor support, were described by Tokitoh, Okazaki et al as well as by Iwamoto and Kira et al, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…179.1 8C; 1 H NMR (395.9 MHz, [D 6 ]benzene, 21.4 8C): d = 1.14 (s, 9 H; tBu), 1.22 (s, 9 H; tBu), 1.23 (s, 9 H; tBu), 1.24 (s, 9 H; tBu), 5.57 (s, 1 H; NC(H)N), 6.80-6.87 (t, 1 H; Ph), 5 H;Ph),6 H;Ph) (H)N), 116.6,118.5,118.7,128.1,128.3,128.4,128.45,128.5,129.4,129.5,133.6,145.5,146.4,148.1 (Ph) : C 68.40, H 7.80, N 11.40; found: C 68.27, H 7.56, N 11.31. (4), C5ÀN1 1.339 (7), C5ÀN2 1.333(6), Si1ÀSi1A 2.384(3); N1-Si1-N2 71.61 (19), N1-Si1-Se1 118.58 (16),, C5-N1-Si1 90.9(3), N2-C5-N1 106.5(4), C5-N2-Si1 91.0(3), Si1A-Si1-N1 109.95 (17).…”
Section: Synthesis Ofmentioning
confidence: 98%
“…Acyloxysilanen [20,23,26] und sind gute Reduktionsmittel fu È r Sa Èu-rechloride und Carbonylverbindungen [20,21]. Der 8-(Dimethylaminomethyl)naphthyl-Substituent ist nicht nur fu È r die Darstellung von pentakoordinierten Siliciumverbindungen geeignet, sondern er erwies sich auch als sehr effizient fu È r die Stabilisierung von Verbindungen mit Si±X-Doppelbindungen (X = N, P, S, Se) [28,29]. Fu È r uns ergab sich die Frage, welchen Einfluû ein 2-(Dimethylaminomethyl)phenyl-bzw.…”
unclassified